Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
x(x-6) = x^2 - 6x
4(x+6) = 4x + 24
First we need to eliminate the bracket by multiplying the numbers and variables from outside the bracket with the inside, we weill get :
X^2 - 6x = 4x + 24
(subtract 4x and 24 from both sides)
x^2 - 10x - 24 = 0
(x+2) (x-12) = 0
x+2 = 0 x-12 = 0
The value of X would be :
x = -2 x = 12
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.